Analysis of the effectiveness of apartment building management in Ukraine: energy efficiency and energy audit - Stanislav Kiris (Економічний вісник Державного вищого навчального закладу Український державний хіміко-технологічний університет, 2021)
The article considers the current situation of housing and communal services of Ukraine in parts of management of apartment buildings. A detailed analysis of the effectiveness of apartment building management in various aspects of management. The organizational efficiency of apartment building management, the efficiency of the regulatory system, the effectiveness of involving co-owners of apartment buildings in management, the efficiency of communications in the management of apartment buildings and energy efficiency are considered. The role of local governments in the process of forming an effective homeowner is determined. The advantages of homeowner from achieving a high level of energy efficiency by the house are analyzed. The goals of the energy audit are indicated. The main reasons for the lack of attention to the formation of the institution of an effective owner in Ukraine are identified. The conditions for the creation and stimulation of a competitive market for the management of apartment buildings, by the introduction of the profession of manager of a residential building (or groups of buildings). There main methods of state support for the introduction of energy efficiency in the management of apartment buildings are subscribed. There are issues that reduce trust in the management of condominiums: low awareness of co-owners of the management of condominiums for their benefit, complete or partial lack of financial reporting of the administration of condominiums to homeowners, lack of constructive dialogue between condominium participants, lack of proper approach to communication administration of condominiums. The problem of uncertainty of the legal status of the land plot under the apartment house and its legal uses is suscribed. The problem of debt collection to condominiums and mechanisms for its solution has been given. The legal framework on this issue, its dynamics and development prospects has been studied. The biggest obstacle to effective reform of the industry is the lack of understanding by both co-owners and managers of the issues and mechanisms of the owner's institution and inefficient housing and communal services in the country.